Static and dynamic hydrophobicity of alumina-based porous ceramics impregnated with fluorinated oil. Issue 14 (4th August 2014) - Tsuruki, Yuta; Sakai, Munetoshi; Isobe, Toshihiro; Matsushita, Sachiko; Nakajima, Akira
Abstract